Pemanfaatan Data Nasabah Untuk Penilaian Risiko Kesehatan Berbasis Riwayat Medis Dengan Metode Kualitatif - Susanti, Harsini; Fazhira, Divatul; Nasution, Zahrah Zhafirah; Supriyatna, Samso (Journal of Information Systems and Business Technology, 2025)
Health risk assessment is a crucial stage in the selection process of health insurance applicants. The development of information systems has enabled insurance companies to manage medical history data more quickly, systematically, and accurately compared to manual methods. This study aims to describe the processes of collecting, inputting, processing, and utilizing medical history data in assessing the health risks of prospective policyholders. The research employed a descriptive qualitative approach through in-depth interviews with a certified insurance agent holding AAJI/AASI certification. The results indicate that the use of information systems accelerates the underwriting process, improves agents’ work efficiency, and supports decision-making in health risk assessment. However, technical issues such as application disruptions and potential data input errors were still identified during implementation. Overall, information systems contribute positively to the quality and effectiveness of health risk assessment processes in insurance companies.